The gastric acid pocket is attenuated in H. pylori infected subjects - Mitchell, David R; Derakhshan, Mohammad H; Wirz, Angela A; Orange, Clare; Ballantyne, Stuart A; Going, James J; McColl, Kenneth E L (Gut, 2017)
ObjectiveGastric acid secretory capacity in different anatomical regions, including the postprandial acid pocket, was assessed in Helicobacter pylori positive and negative volunteers in a Western population.DesignWe studied 31 H. pylori positive and 28 H. pylori negative volunteers, matched for age, gender and body mass index. Jumbo biopsies were taken at 11 predetermined locations from the gastro-oesophageal junction and stomach. Combined high-resolution pH metry (12 sensors) and manometry (36 sensors) was performed for 20 min fasted and 90 min postprandially. The squamocolumnar junction was marked with radio-opaque clips and visualised radiologically. Biopsies were scored for inflammation and density of parietal, chief and G cells immunohistochemically.ResultsUnder fasting conditions, the H. pylori positives had less intragastric acidity compared with negatives at all sensors >1.1 cm distal to the peak lower oesophageal sphincter (LES) pressure (p<0.01). Postprandially, intragastric acidity was less in H. pylori positives at sensors 2.2, 3.3 and 4.4 cm distal to the peak LES pressure (p<0.05), but there were no significant differences in more distal sensors. The postprandial acid pocket was thus attenuated in H. pylori positives. The H. pylori positives had a lower density of parietal and chief cells compared with H. pylori negatives in 10 of the 11 gastric locations (p<0.05). 17/31 of the H. pylori positives were CagA-seropositive and showed a more marked reduction in intragastric acidity and increased mucosal inflammation.ConclusionsIn population volunteers, H. pylori positives have reduced intragastric acidity which most markedly affects the postprandial acid pocket.